Investing in education in Europe: Evidence from a new survey of public opinion. (February 2018) - Busemeyer, Marius R.; Garritzmann, Julian L.; Neimanns, Erik; Nezi, Roula
Public opinion research has found that increasing the investment in education is generally very popular among citizens in Western Europe. However, this evidence from publicly available opinion surveys may be misleading, because these surveys do not force respondents to prioritize between different parts of the education system or between education and other social policies, nor do they provide information about citizens' willingness to pay for additional investment in education. To address these deficiencies, we conducted an original, representative survey of public opinion on education and related policies in eight European countries. Our analysis confirms that citizens express high levels of support for education even when they are forced to choose between education and other areas of social spending. But not all educational sectors enjoy equally high levels of support: increasing spending on general schooling and vocational education is more popular than increasing spending on higher education and early childhood education. Furthermore, we find that citizens are, in fact, willing to pay additional taxes in order to finance investment in education, at least in some countries and for some sectors of the education system.